PROPOLIS: CHEMICAL COMPOSITION, BIOLOGICAL AND PHARMACOLOGICAL ACTIVITY – A REVIEW - Stojanović, Sanja T; Najman, Stevo J; Bogdanova Popov, Biljana; Najman, Svetozar S (Acta medicae Medianae, 2020)
Propolis is a honey bee product that is well known from ancient times for its beneficial effects on human health and has been widely used in traditional medicine. Chemical composition of propolis is very complex and rich which is why propolis has many biological activities, but is dependent on the geographical origin and plant sources from which bees collect it. Despite great diversity of its chemical composition, propolis has many biological and pharmacological activities and is widely used in medicine, dentistry and pharmacy. In this review, beneficial effects of propolis through its biological and pharmacological activities are discussed.